Getting StartED with Google Apps - Darbyshire, Paul; Darbyshire, Adam (Apress : Imprint: Apress, 2010)
How would you like to share your calendar, access your e-mail, or create and share documents, all online from your smartphone/mobile device, netbook, or desktop? If you answered yes, then you should know that the best of all these online applications and services are being offered for free, from one of the Internet's biggest names, Google. These apps are in an online suite of productivity and fun applications called Google Apps. Getting StartED with Google Apps gets you started collaborating and creating with Google's online suite of applications on the Chrome operating system-analogous to using Microsoft Office on Windows. The differences are that Google Apps and Chrome are mostly free and run entirely on the Web. With this book, you get clear and easy-to-use instructions for getting up and running with basic Google Apps like Gmail, Google Voice, and more. Moreover, you get detailed visuals and step-by-step explanations on the more sophisticated Google apps like Google Docs, Spreadsheets, Presentations, SketchUp, and more. So get going and have some fun while you're at it.